Polysaccharide fraction from greens of Raphanus sativus alleviates high fat diet-induced obesity. (1st May 2021) - Do, Moon Ho; Lee, Hye-Bin; Oh, Mi-Jin; Jhun, Hyunjhung; Choi, Sang Yoon; Park, Ho-Young
Highlights: Polysaccharide fraction of radish greens (PRG) were prepared and characterized. PRG reduced high fat diet-induced body weight gain and body fat percentage. PRG restored gut barrier function and colon shortening by gut microbiota modulation. PRG regulated lipid metabolism in white adipose tissue and reduced adipocyte size. Abstract: Radish ( Raphanus sativus ) greens are commonly used as a vegetable in Korea; however, their anti-obesity effect has not been reported yet. We prepared the polysaccharide fraction of radish greens (PRG) and assessed its anti-obesity activity in high fat diet (HFD)-induced obese C57BL/6J mice. Supplementation with 4 mg/kg PRG reduced weight gain and body fat percentage, and regulated serum biomarkers against HFD-induced obesity. Moreover, PRG treatment improved gut permeability by increasing tight junction protein expression and colon length shortening. HFD intake increased the proportion of Firmicutes and decreased the proportion of Bacteroidetes and Verrucomicrobia; however, PRG supplementation maintained gut microbial composition to normal diet condition. Moreover, PRG reduced HFD-induced increase of lipid metabolism-related protein expression, along with adipocyte size in white adipose tissue. These results indicated that PRG as a potential prebiotic, has anti-obesity properties by improving gut barrier function, modulating gut microbiota and regulating lipid metabolism.